2004
DOI: 10.1007/s00015-004-1137-2
|View full text |Cite
|
Sign up to set email alerts
|

Decapod crustaceans from the Middle Jurassic Opalinus Clay of northern Switzerland, with comments on crustacean taphonomy

Abstract: Four species of decapod crustaceans from the Middle Jurassic Opalinus Clay (Aalenian) of Northern Switzerland are described. Of these, Mecochirus cf. eckerti is the most common one, while Eryma cf. bedelta, Glyphea sp. and Aeger sp. were present as individuals, or only a few specimens. The preservation of these crustaceans ranges from moderate to excellent, reflecting the favourable taphonomic conditions of the depositional environment. An interesting aspect of the taphocoenosis in the Opalinus Clay is that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
(29 reference statements)
1
7
0
1
Order By: Relevance
“…Serious oxygen-depletion of the bottom-water and high sediment accumulation rates were responsible for the sometimes exceptional preservation of fossils including articulated arthropods, articulated echinoderms and vertebrates and preservation of organic materials like the ligament of bivalves and the periostracum of ammonites as well as other molluscs (e.g., Etter 1988Etter , 1990Etter , 1995Etter , 2004a.…”
Section: Geological Setting and Taphonomymentioning
confidence: 99%
See 1 more Smart Citation
“…Serious oxygen-depletion of the bottom-water and high sediment accumulation rates were responsible for the sometimes exceptional preservation of fossils including articulated arthropods, articulated echinoderms and vertebrates and preservation of organic materials like the ligament of bivalves and the periostracum of ammonites as well as other molluscs (e.g., Etter 1988Etter , 1990Etter , 1995Etter , 2004a.…”
Section: Geological Setting and Taphonomymentioning
confidence: 99%
“…In southern Germany and northern Switzerland, the Opalinus Clay is exposed in several clay pits and a few natural exposures. This formation is characterized by a rather low benthic diversity, well-preserved arthropods and the rare preservation of articulated echinoderms and vertebrate skeletons (e.g., Etter 1988Etter , 1990Etter , 1995Etter , 1996Etter , 2004a. The name of this lithostratigraphic unit derives from the locally abundant ammonite Leioceras opalinum, whose species name refers to the opal-like nacre preservation widely found in central Europe (Quenstedt 1843).…”
Section: Introductionmentioning
confidence: 99%
“…This is the oldest record of a mecochirid from South America, and the first one for Argentina, and considerably extends the palaeogeographic distribution of the genus Beurlen 1928;Carter 1886Carter , 1898Collins and Rasmussen 1992;Etter 2004;Feldmann and Keyes 1992;Feldmann et al 2007;Förster 1971;Förster and von Hillebrandt 1984;Frentzen 1937;Garassino 1996;Garassino and Schweigert 2006;Glaessner 1929Glaessner , 1960Hée 1924;Herrick and Schram 1978;Krause 1891;Oppel 1862;Quenstedt 1854Quenstedt , 1856Quenstedt -1857Secretan 1964Secretan , 1968van Straelen 1924van Straelen , 1936Taylor 1979;da Veiga Ferreira 1955;Woodward 1876 New early Jurassic decapod crustacean from Patagonia (Chubut province), Argentina 151 during the Early Jurassic, previously known only from Europe by that time.…”
Section: Discussionmentioning
confidence: 96%
“…5). By contrast, very little is known of the geographic distribution of the genus during the Early and Middle Jurassic, when up to now it was only known from Europe (Quenstedt 1854, 1856-1857, Oppel 1862Carter 1886;Krause 1891;van Straelen 1924;Beurlen 1928;Glaessner 1929;Frentzen 1937;Förster 1971;Etter 2004;Garassino 1996). Nevertheless, Feldmann and Schweitzer (2006) indicated that Mecochirus ''had its earliest occurrence in the North Atlantic in Sinemurian time but radiated into the Southern Hemisphere by the Toarcian,'' but they did not provide any evidence to back this statement.…”
Section: Palaeobiogeographymentioning
confidence: 86%
“…It is known by many fossils supporting the greatest number of described species among Erymidae Van Straelen, 1925(Schweitzer et al, 2010Hyžn y et al, 2015). Eryma is well known in European Jurassic and Early Cretaceous deposits (Carter, 1886;Étallon, 1859Oppel, 1861Oppel, , 1862Ferry, 1865;Krause, 1891;Lahusen, 1894;Harbort, 1905;Van Straelen, 1920, 1925Hée, 1924;Beurlen, 1928;Woods, 1925Woods, -1931Birshtein, 1956;Förster, 1965Förster, , 1966Martill, 1991;Garassino, 1996;Schweigert et al, 2000;Fischer, 2003;Etter, 2004;Carpentier et al, 2006;Garassino and Schweigert, 2006;Charbonnier, 2009;Schweitzer et al, 2009;Charbonnier et al, 2010Charbonnier et al, , 2012Charbonnier et al, , 2014Bravi et al, 2014;Devillez et al, 2016), and some occurrences are also reported throughout the world: in Middle East (Roger, 1946;Förster and Seyed-Emani, 1982;Garassino, 1994), in Africa (Beurlen, 1933;Secrétan, 1984), in North America (Rathbun, 1923(Rathbun, , 1926Feldm...…”
Section: Introductionmentioning
confidence: 99%